THE HIERARCHY OF NEEDS PORTRAYED IN JIM PRESTON’S CHARACTER IN PASSENGERS (2016) FILM - Yupita Citra; M. Natsir; Anjar Dwi Astuti (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2020)
ABSTRACT This research is intended to find out the needs of Jim’s character which was portrayed in Passengers (2016) film. It was also to identify the fulfilment of his needs based on five stages of Maslow’s Hierarchy of Needs. The theory that is used to analyze the main character in this film was the hierarchy of needs theory. It was Abraham Maslow’s theory which consists of five stages of human needs. The researcher used descriptive qualitative method by Elo and Kyngas. The result of this research shows Jim fulfilled five of his needs, which are physiological needs, safety needs, belongingness and love needs, self-esteem, and self-actualization. There were moments where he has fulfilled higher stage of needs, but another needs from the lower stage appear. For example, at some scenes he fulfilled his love and belongingness needs by waking Aurora up and some sparks of love appear between them. When Arthur the bartender robot told Aurora the truth that Jim was the one who took her life from her, Jim back to the stage where he has love and belongingness needs. Jim also actualized himself as a mechanic, a rate two mechanic, which he thought was useful on the starship. Even though he has reached the highest stage of hierarchy of needs, another needs from lower stage appeared. Safety needs appeared when the starship got hit by a huge meteor and damages multiple parts of the starship at once.  ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui kebutuhan dari karakter Jim yang di gambarkan dalam film Passengers (2016). Selain itu juga untuk mengidentifikasi pemenuhan dari kebutuhannya berdasarkan lima tingkatan Hierarchy of Needs dari Maslow. Teori yang digunakan untuk menganalisa karakter utama dalam film ini adalah teori Hierarchy of Needs yang terdiri dari lima tingkatan kebutuhan manusia. Peneliti menggunakan metode kualitatif deskriptif oleh Elo dan Kyngas. Hasil penelitian ini menunjukan Jim memenuhi lima kebutuhannya, yaitu kebutuhan fisiologi, kebutuhan keamanan, kebutuhan akan rasa memiliki dan cinta, harga diri, dan aktualisasi diri. Ada saat-saat dimana ia telah memenuhi kebutuhan di tingkat yang lebih tinggi, namun kebutuhan dari tingkat lebih rendah muncul. Misalnya, pada beberapa adegan ia telah memenuhi kebutuhan akan cinta dan rasa memiliki dengan membangunkan Aurora dan cinta muncul diantara mereka. Saat Arthur sang bartender memberitahu Aurora bahwa Jim adalah orang yang merenggut hidupnya darinya, Jim kembali ke tahap dimana ia memliki kebutuhan akan cinta dan rasa memiliki. Jim juga mengaktualisasikan dirinya sebagai mekanik, mekanik tingkat dua, yang menurutnya akan berguna di pesawat luar angkasa. Meskipun ia telah mencapai tingkat tertinggi dari Hierarchy of Needs, kebutuhan lain dari tingkatan lebih rendah muncul. Kebutuhan akan keamanan muncul ketika kapal luar angkasa tekena meteor besar dan merusak beberapa bagian kapal luar angkasa. Kata kunci: Hierarchy of Needs, Karakter, Karakterisasi, Passengers